Risk Factors for Prolonged Length of Hospital Stay and Readmissions After Laparoscopic Sleeve Gastrectomy and Laparoscopic Roux-en-Y Gastric Bypass - Major, Piotr (Obes Surg, 2017)
BACKGROUND: Laparoscopic sleeve gastrectomy (LSG) and laparoscopic gastric bypass (LRYGB) are most commonly performed bariatric procedures. Laparoscopic approach and enhanced recovery after surgery (ERAS) protocols managed to decrease length of hospital and morbidity. However, there are patients in whom, despite adherence to the protocol, the length of stay (LOS) remains longer than targeted. This study aimed to assess potential risk factors for prolonged LOS and readmissions. METHODS: The study was a prospective observation with a post-hoc analysis of bariatric patients in a tertiary referral university teaching hospital. Inclusion criteria were undergoing laparoscopic bariatric surgery. Exclusion criteria were occurrence of perioperative complications, prior bariatric procedures, and lack of necessary data. The primary endpoints were the evaluations of risk factors for prolonged LOS and readmissions. RESULTS: Median LOS was 3 (2–4) days. LOS > 3 days occurred in 145 (29.47%) patients, 79 after LSG (25.82%) and 66 after LRYGB (35.48%; p = 0.008). Factors significantly prolonging LOS were low oral fluid intake, high intravenous volume of fluids administered on POD0, and every additional 50 km distance from habitual residence to bariatric center. The risk of hospital readmission rises with occurrence of intraoperative adverse events and low oral fluid intake on the day of surgery on. CONCLUSIONS: Risk factors for prolonged LOS are low oral fluid intake, high intravenous volume of fluids administered on POD0, and every additional 50 km distance from habitual residence. Risk factors for hospital readmission are intraoperative adverse events and low oral fluid intake on the day of surgery.